Infant Trauma Management in the Emergency Department: An Emergency Medicine Simulation Exercise - Mathieson, Sarah (Cureus, 2015)
In a trauma situation, it is essential that emergency room physicians are able to think clearly, make decisions quickly and manage patients in a way consistent with their injuries. In order for emergency medicine residents to adequately develop the skills to deal with trauma situations, it is imperative that they have the opportunity to experience such scenarios in a controlled environment with aptly timed feedback. In the case of infant trauma, sensitivities have to be taken that are specific to pediatric medicine. The following describes a simulation session in which trainees were tasked with managing an infantile patient who had experienced a major trauma as a result of a single vehicle accident. The described simulation session utilized human patient simulators and was tailored to junior (year 1 and 2) emergency medicine residents.